Plastic flash resin capable of detecting < 90 > Sr as well as preparation method and application of plastic flash resin

By using plastic scintillation resin containing plastic scintillation microspheres and strontium extractant, the integrated separation and detection of 90Sr is achieved, which solves the problems of independent detection process, long time-consuming and difficult waste liquid treatment in traditional methods, and achieves rapid and automated and environmental testing results.

CN119350775APending Publication Date: 2025-01-24LANZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411897641.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art has problems in the detection of 90Sr that are independent of separation and measurement processes, time-consuming, difficult to achieve automation, and the generation of radioactive organic waste liquid.

Method used

A plastic flash resin, including plastic flashing micro -balls and pyrine extracts, prepare plastic flashing microspheres by aggregating reaction, and adsorb the ingredients to its surface and internal pores to achieve the integration and detection of 90SR.

Benefits of technology

The testing process was simplified, the analysis time was shortened, and the generation of radioactive organic waste solution was avoided, and it was easy to achieve automation and online monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350775A_ABST
    Figure CN119350775A_ABST
Patent Text Reader

Abstract

The invention provides plastic flash resin capable of detecting < 90 > Sr as well as a preparation method and application of the plastic flash resin, and belongs to the technical field of plastic flash resin. The plastic scintillation resin provided by the invention comprises plastic scintillation microspheres and a strontium extraction agent positioned on the surfaces and internal pores of the plastic scintillation microspheres, the plastic scintillating microsphere comprises a plastic matrix and a scintillating agent. According to the invention, N, N, N ', N'-tetraisobutyl-3-oxoglutaramide is used as a strontium extraction agent, and has an effect of selectively adsorbing strontium. The plastic flash resin provided by the invention has good detection performance on 90Sr, can integrally adsorb and detect 90Sr, simplifies the detection process, shortens the measurement time of 90Sr, is low in price, and can be stored for a long time. Compared with traditional liquid flashing, the plastic flashing resin provided by the invention does not generate radioactive organic waste liquid when measuring 90Sr, and is easy to realize material reutilization and easy to realize automatic and on-line monitoring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of plastic flash resin, and in particular to a detectable 90 Sr plastic flash resin and its preparation method and application. Background Art

[0002] With the rapid development of the global economy and the continuous growth of population, people's energy demand is increasing day by day. The development and utilization of nuclear energy has become the preferred way for many countries in the world to solve the energy crisis. The rapid detection and online monitoring of radioactive nuclides in the solution is one of the keys to ensure the normal operation of nuclear facilities. 90 Sr is an important nuclide to consider in nuclear facility effluent management and environmental monitoring due to its biological and radiotoxicity.

[0003] In the traditional 90 In the Sr analysis and measurement method, in order to 90 The Sr concentration meets the analytical measurement requirements, and the matrix and other nuclides are excluded. 90 The influence of Sr measurement on 90 Before Sr measurement, some chemical methods are needed to 90 Sr is enriched and separated from other elements. At present, the main methods for separation and enrichment of strontium include nitrate precipitation separation, solvent extraction, extraction chromatography, etc. However, these methods make the separation and measurement processes independent of each other, resulting in these methods being time-consuming and difficult to automate, and these methods will produce radioactive organic waste liquid, which is difficult to handle.

[0004] for 90 The most widely used methods for the measurement of Sr are various types of mass spectrometers and liquid scintillation counters (LSC). 90 Sr is susceptible to its isotopic 90 Interference from Zr and polyatomic ions. 90 Sr has a high detection efficiency, but liquid scintillation counters will experience a certain degree of quenching in practical applications, and liquid scintillation measurement will produce a large amount of radioactive organic waste liquid, which is difficult to handle. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a detectable 90 Sr plastic flash resin and its preparation method and application. 90 Sr plastic flash resin can be separated and detected in one, simplifying the detection process and shortening the analysis time.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a detectable90 The plastic scintillating resin of Sr is characterized by comprising plastic scintillating microspheres and a strontium extractant located on the surface and internal pores of the plastic scintillating microspheres; The plastic scintillation microspheres include a plastic matrix and a scintillator dispersed in the plastic matrix; The strontium extractant is N,N,N',N'-tetraisobutyl-3-oxoglutaramide.

[0007] Preferably, the material of the plastic matrix is ​​one or more of polystyrene, styrene-divinylbenzene copolymer, polydivinylbenzene and polyvinyltoluene; The scintillator is one or more of 2,5-diphenyloxazole, 2-(4-biphenylyl)-5-phenyloxadiazole and 2-(4-biphenylyl)-5-(4-tolyl)-1,3,4-oxadiazole.

[0008] Preferably, the mass of the scintillator is 0.5-3% of the mass of the plastic matrix.

[0009] Preferably, the particle size of the plastic scintillation microspheres is 100-300 μm.

[0010] Preferably, the mass of the strontium extractant is 15-50% of the mass of the plastic scintillation microspheres.

[0011] The present invention provides the above-mentioned detectable 90 The preparation method of Sr plastic flash resin comprises the following steps: (1) Mixing an unsaturated plastic monomer, a scintillator and an initiator to obtain an oil phase mixed liquid; (2) heating and mixing the emulsifier and water to obtain an aqueous phase mixture; (3) adding the oil phase mixed liquid to the water phase mixed liquid to carry out a polymerization reaction to obtain plastic scintillation microspheres; (4) mixing the plastic scintillation microspheres with an alcohol solution of a strontium extractant, removing the alcohol solvent after the strontium extractant is adsorbed by the plastic scintillation microspheres, and obtaining a detectable 90 Sr plastic flash resin; There is no order of precedence for steps (1) to (2).

[0012] Preferably, the polymerization reaction temperature is 70-90° C. and the time is 6 h.

[0013] Preferably, the alcohol solvent is removed by rotary evaporation at a temperature of 50-70°C.

[0014] The present invention provides the above-mentioned detectable 90 Sr plastic flash resin in adsorption and detection 90 Application in Sr.

[0015] Preferably, the adsorption 90 Sr was tested in a 0.5~1 mol / L nitric acid environment.

[0016] The present invention provides a detectable 90 The invention discloses a plastic scintillator resin for Sr, comprising a plastic scintillator microsphere and a strontium extractant located on the surface and internal pores of the plastic scintillator microsphere; the plastic scintillator microsphere comprises a plastic matrix and a scintillator dispersed in the plastic matrix; the strontium extractant is N,N,N',N'-tetraisobutyl-3-oxoglutaramide. The invention uses N,N,N',N'-tetraisobutyl-3-oxoglutaramide as a strontium extractant, which has a large distribution ratio for strontium and can effectively adsorb 90 Sr. Scintillator can receive 90 Sr emits β rays and produces fluorescence, which is received by the photomultiplier tube of the instrument to achieve measurement. 90 The purpose of Sr. The present invention provides a detectable 90 Sr plastic flash resin 90 Sr has good detection performance and can be integrated for adsorption and detection 90 Sr, simplifies the detection process and shortens 90 The measurement time of Sr is short, the price is low and it can be stored for a long time. Compared with the traditional liquid scintillator, the detectable 90 Measurement of Sr in Plastic Flash Resin 90 Sr does not produce radioactive organic waste liquid, and it is easy to reuse the material, and easy to realize automation and online monitoring. 90 The rapid detection and online monitoring of Sr provides a new method with good application prospects.

[0017] Furthermore, the present invention provides a detectable 90 Sr plastic flash resin can separate and measure strontium under low acidity conditions, which is of great significance for the detection and monitoring of actual radionuclide contaminated water bodies.

[0018] The present invention provides the above-mentioned detectable 90 The invention discloses a method for preparing Sr plastic flash resin, which has the advantages of simple operation, low cost and easy to realize industrialized mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 For Example 1, it can be detected 90 SEM scanning images of Sr plastic scintillating resin and plastic scintillating microspheres of comparative example 1; Figure 2 For Example 1, it can be detected 90 Infrared characterization of Sr plastic scintillating resin and plastic scintillating microspheres of comparative example 1; Figure 3 For Example 1, it can be detected 90 Fluorescence emission spectra of Sr plastic flash resin and comparative example 2 resin; Figure 4 For Example 1, it can be detected 90 Adsorption isotherm of Sr on plastic flash resin at 25℃; Figure 5 For Example 1, it can be detected 90 The counts of Sr in plastic flash resin and the addition 90 Standard curve of Sr radioactivity; Figure 6 For Example 1, it can be detected 90 The effect diagram of the storage time stability of Sr plastic flash resin; Figure 7 For Example 1, it can be detected 90 Effect diagram of the particle size of Sr plastic flash resin on the detection effect; Figure 8 For Example 1, it can be detected 90 The adsorption effect of Sr plastic flash resin on strontium under different acidity conditions; Fig. 9 The figure is a comparison of strontium adsorption rates in Examples 1 to 4. DETAILED DESCRIPTION

[0020] The present invention provides a detectable 90 Sr plastic scintillator resin, comprising plastic scintillator microspheres and strontium extractants located on the surface and internal pores of the plastic scintillator microspheres; The plastic scintillation microspheres include a plastic matrix and a scintillator dispersed in the plastic matrix; The strontium extractant is N,N,N',N'-tetraisobutyl-3-oxoglutaramide.

[0021] In the present invention, the plastic scintillation microspheres include a plastic matrix and a scintillator. In the present invention, the material of the plastic matrix is ​​preferably one or more of polystyrene, styrene-divinylbenzene copolymer, polydivinylbenzene and polyvinyltoluene, more preferably polystyrene; the monomers for preparing the plastic matrix preferably include styrene and / or vinyltoluene, more preferably styrene.

[0022] In the present invention, the scintillator is preferably one or more of 2,5-diphenyloxazole, 2-(4-biphenyl)-5-phenyloxadiazole and 2-(4-biphenyl)-5-(4-tolyl)-1,3,4-oxadiazole. In the present invention, the mass of the scintillator is preferably 0.5-3% of the mass of the plastic substrate, more preferably 1-2%. As a specific embodiment of the present invention, the mass of the scintillator is 0.5%, 1%, 1.5%, 2%, 2.5% or 3% of the mass of the plastic substrate. In the present invention, the role of the scintillator is to receive 90 Sr emits β rays and produces fluorescence, which is received by the photomultiplier tube of the instrument to achieve measurement. 90 The purpose of Sr.

[0023] In the present invention, the particle size of the plastic scintillating microspheres is preferably 100-300 μm, more preferably 100-200 μm; as a specific embodiment of the present invention, the particle size of the plastic scintillating microspheres is 100 μm, 150 μm, 200 μm, 250 μm or 300 μm.

[0024] In the present invention, the strontium extractant is an amide substance, specifically N,N,N',N'-tetraisobutyl-3-oxoglutaramide (TiBOPDA). In the present invention, the mass of the strontium extractant is preferably 15-50% of the mass of the plastic scintillating microspheres. As a specific embodiment of the present invention, the mass of the strontium extractant is 15%, 25%, 30%, 35%, 40%, 45% or 50% of the mass of the plastic scintillating microspheres.

[0025] The present invention provides the above-mentioned detectable 90 The preparation method of Sr plastic flash resin comprises the following steps: (1) Mixing an unsaturated plastic monomer, a scintillator and an initiator to obtain an oil phase mixed liquid; (2) heating and mixing the emulsifier and water to obtain an aqueous phase mixture; (3) adding the oil phase mixed liquid to the water phase mixed liquid to carry out a polymerization reaction to obtain plastic scintillation microspheres; (4) mixing the plastic scintillation microspheres with an alcohol solution of a strontium extractant, removing the alcohol solvent after the strontium extractant is adsorbed by the plastic scintillation microspheres, and obtaining a detectable 90 Sr plastic flash resin.

[0026] The present invention has no special requirements on the preparation order of the oil phase mixed liquid and the water phase mixed liquid.

[0027] The present invention mixes an unsaturated plastic monomer, a scintillator and an initiator to obtain an oil phase mixed liquid. In the present invention, the unsaturated plastic monomer is preferably one or more of styrene, divinylbenzene and vinyltoluene. When the unsaturated plastic monomer is two or more of the above, the present invention has no special requirements on their ratio.

[0028] In the present invention, the initiator is preferably one or more of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate. In the present invention, the mass of the initiator is preferably 1-3% of the mass of the unsaturated plastic monomer.

[0029] The present invention has no special requirements for the mixing method, and any mixing method known in the art may be used, such as ultrasonic mixing.

[0030] In the present invention, an emulsifier and water are heated and mixed to obtain an aqueous phase mixture. In the present invention, the emulsifier is preferably polyvinyl alcohol; in the present invention, the mass of the polyvinyl alcohol is preferably 0.5% to 2% of the mass of water, and more preferably 0.5%. In the present invention, the temperature of the heating and mixing is preferably 70 to 90°C. As a specific embodiment of the present invention, the temperature of the heating and mixing is 70°C, 80°C or 90°C.

[0031] The present invention adds the oil phase mixture to the water phase mixture to perform a polymerization reaction to obtain plastic scintillation microspheres. In the present invention, the mass of the oil phase mixture is preferably 8-15% of the mass of the water phase mixture, specifically 8%, 10%, 12% or 15%.

[0032] The present invention preferably performs the polymerization reaction under stirring, and the stirring rate is preferably 300 rpm. In the present invention, the polymerization reaction temperature is preferably 70-90°C, more preferably 80°C, and the time is preferably 5-10h, more preferably 6-8h.

[0033] After the polymerization reaction, the present invention preferably washes and dries the obtained polymerization product to obtain plastic scintillation microspheres. In the present invention, the washing is preferably washing with warm deionized water for multiple times; the drying is preferably oven drying, and the drying temperature is preferably 60°C.

[0034] The present invention mixes the plastic scintillation microspheres with an alcohol solution of a strontium extractant, removes the alcohol solvent, and obtains a detectable 90In the present invention, the concentration of the strontium extractant in the alcohol solution of the strontium extractant is preferably 0.2-1 mol / L. As a specific embodiment of the present invention, the concentration of the strontium extractant is preferably 0.2 mol / L, 0.5 mol / L, 0.8 mol / L or 1 mol / L. In the present invention, in the alcohol solution of the strontium extractant, the alcohol solvent is preferably one or more of methanol, ethanol and n-octanol.

[0035] In the present invention, the mixing method is preferably shaking mixing. In the present invention, the shaking mixing time is preferably 24h.

[0036] In the present invention, the method for removing the alcohol solvent is preferably rotary evaporation. In the present invention, the temperature of the rotary evaporation is preferably 50-70°C. As a specific embodiment of the present invention, the temperature of the rotary evaporation is 50°C, 60°C or 70°C. The present invention has no special requirements for the time of the rotary evaporation, as long as the alcohol solvent is fully removed.

[0037] The present invention provides the above-mentioned detectable 90 Sr plastic flash resin in adsorption and detection 90 In the present invention, the adsorption 90 The Sr reaction is preferably carried out under low acidity conditions, and more specifically, in a 0.5-1 mol / L nitric acid environment.

[0038] The detectable 90 The Sr plastic flash resin and its preparation method and application are described in detail, but they should not be understood as limiting the scope of protection of the present invention.

[0039] Example 1 (1) Preparation of plastic scintillating microspheres Preparation of aqueous phase mixture: Take 120 mL of deionized water in a 250 mL round-bottom flask, add 0.6 g of polyvinyl alcohol, and heat to 80°C.

[0040] Preparation of oil phase mixture: weigh 7.5 g styrene and 2.5 g divinylbenzene in a reagent bottle, mix well, weigh 0.1 g scintillator 2,5-diphenyloxazole (PPO) and 0.1 g azobisisobutyronitrile (AIBN), and ultrasonically oscillate for 20.00 min until all reagents are dissolved evenly and set aside.

[0041] The prepared oil phase mixture was added to the water phase mixture, mechanically stirred at 300 rpm, slowly heated to 80.00°C, and kept warm for 6.00 h to obtain a crude resin product. The crude product was washed with warm deionized water for several times until the upper aqueous solution was clear, and then dried in an oven at 60°C to obtain plastic scintillating microspheres.

[0042] (2) Detectable 90 Preparation of Sr-containing plastic resin Dissolve 0.25 g of strontium extractant N,N,N',N'-tetraisobutyl-3-oxoglutaramide in 45 mL of ethanol, add 1 g of plastic scintillation microspheres, shake thoroughly at 60 ° C, and then evaporate the ethanol by rotary evaporation to obtain a detectable 90 Sr plastic flash resin.

[0043] Comparative Example 1 The difference from Example 1 is that after obtaining the plastic scintillation microspheres in step (1), the next step is not performed.

[0044] Comparative Example 2 The difference from Example 1 is that in the preparation of the plastic scintillating microspheres in step (1), no scintillator PPO is added.

[0045] Comparative Example 3 The scintillation resin was synthesized according to the method described in Example 1 of the patent "A scintillation resin with dual functions of separation and detection of strontium-90 and its preparation method and application" (application number: CN 202311004128.0). 90 Sr dual-function scintillating resin. The specific method is as follows: (1) Preparation of aqueous solution 100 mL of deionized water was measured and placed in a round-bottom flask, and 0.5% of polyvinyl alcohol by mass of the deionized water was added thereto, and the mixture was heated to 80°C to completely dissolve the polyvinyl alcohol, and then cooled to 60°C to obtain an aqueous phase solution; (2) Preparation of oil phase mixed solution Weigh 7.5g of styrene and 2.5g of divinylbenzene into a reagent bottle and mix them evenly. Add 1.00% of 2,5-diphenyloxazole (PPO) and 0.04% of 1,4-bis(5-phenyloxazole)benzene (POPOP) to the solution, respectively. Add 1.00% of azobisisobutyronitrile to the total mass of styrene and divinylbenzene, dissolve and shake well, and then add 25% of 4,4(5)-di-tert-butyl-dicyclohexyl-18-crown-6 (DtBuCH 18 C6) shaking to obtain an oil phase mixed solution; (3) Suspension polymerization The prepared oil phase mixed solution and water phase solution were added to a 250 mL round-bottom flask, mechanically stirred at 300 rpm at room temperature until a uniform emulsion was formed, and then heated to 90 ° C for suspension polymerization for 6 h. The product was washed several times with 80 ° C deionized water until the upper aqueous solution was clear, and then dried at room temperature for 24 h to obtain 90Sr bifunctional scintillating resin (PSresin).

[0046] Example 2 The difference from Example 1 is that the amount of strontium extractant used is 15% of the plastic scintillation microspheres.

[0047] Example 3 The difference from Example 1 is that the amount of strontium extractant used is 35% of the plastic scintillation microspheres.

[0048] Example 4 The difference from Example 1 is that the amount of strontium extractant used is 45% of the plastic scintillation microspheres.

[0049] Performance Testing (1) Detectable 90 SEM scanning image of Sr plastic flash resin Example 1 Preparation of detectable 90 The SEM images of the plastic scintillating resin of Sr and the plastic scintillating microspheres prepared in Comparative Example 1 are shown in FIG. Figure 1 shown. Figure 1 In the figure, (a) and (b) are SEM images of comparative example 1, and (c) and (d) are SEM images of embodiment 1. It can be seen that 90 Sr plastic scintillator resin and plastic scintillator microspheres are both complete and full spheres, with particle sizes mainly ranging from 100 to 300 μm. The surface of the plastic scintillator microspheres is smooth and flat, which can be detected. 90 The surface of the Sr plastic flash resin sphere is obviously rough and uneven, and there are a lot of depressions, which increases the detectable 90 The specific surface area of ​​Sr plastic flash resin is conducive to the detection 90 Adsorption of strontium by Sr-based plastic flash resin.

[0050] (2) Detectable 90 Infrared Characterization of Sr-containing Plastic Flash Resin Example 1 Preparation of detectable 90 The infrared spectra of the plastic scintillating resin of Sr and the plastic scintillating microspheres prepared in Comparative Example 1 are as follows: Figure 2 As shown. It can be seen that both use styrene as the polymerization monomer, and they can be observed to have many overlapping characteristic peaks in the infrared spectrum. Comparing the infrared spectra of the two, it can be found that the detectable 90 Sr plastic flash resin at 1650 cm -1 , 1120 cm -1 New absorption peaks appeared at 20° and 10°, which were caused by the stretching vibrations of C=O and C—O—C bonds in the extractant, respectively. This confirmed that the extractant TiBOPDA, which adsorbed strontium, was successfully combined with the detectable 90 Sr's plastic flash resin.

[0051] (3) Detectable90 Fluorescence emission spectrum of Sr-containing plastic resin Example 1 Preparation of detectable 90 The fluorescence emission spectra of the Sr plastic scintillator resin and the scintillator-free resin prepared in Comparative Example 2 are as follows: Figure 3 As shown. It can be seen that the detectable 90 The maximum fluorescence emission intensity of the Sr plastic scintillator resin is around 415 nm, which is within the optimal detection range of the photomultiplier tube, while the resin without scintillator (Comparative Example 2) has no fluorescence emission peak in this range. 90 Sr plastic flash resin has good fluorescence properties.

[0052] (4) Detectable 90 Adsorption isotherm of Sr on plastic resin at 25℃ Take 50 mg of the detectable 90 Sr plastic flash resin, add 5 mL of strontium solution. Detectable at 25℃ 90 The adsorption capacity of Sr plastic flash resin (q e ) and the equilibrium concentration of strontium (C e ) is like the relationship between Figure 4 As shown. It can be seen that with the increase of strontium concentration, the detectable 90 The adsorption capacity of Sr plastic flash resin for strontium gradually increases and then tends to be stable, which can be detected 90 The maximum adsorption capacity of Sr plastic flash resin for strontium is 7.39 mg / g.

[0053] (5) 90 Standard curve of Sr activity and liquid scintillation counting Will contain 90 The solution of Sr can be detected by Example 1 90 The resin column composed of Sr plastic flash resin, 90 Sr is adsorbed on the resin column, and then the resin column is drained and placed in a liquid scintillation bottle. Finally, the liquid scintillation bottle containing the resin column is placed in a liquid scintillation counter to measure 90 The amount of Sr. 90 The counts of Sr in the plastic flash resin are different from those of 90 The standard curve of Sr radioactivity is as follows Figure 5 As shown. It can be seen that the addition of 90 The activity of Sr has a good linear relationship with the liquid scintillation count. 2 = 0.997. This shows that the present invention can detect 90 Detection of Sr in plastic flash resin 90 The Sr radioactivity method is feasible.

[0054] (6) Detectable 90 Storage stability of Sr-containing plastic resin Referring to the method in (5) above, 90 Sr adsorption can be detected 90 After the Sr plastic scintillation resin is applied, the counting results obtained by liquid scintillation measurement are as follows when the liquid scintillation measurement is stored for 0 to 15 days: Figure 6 It can be seen that when the storage time is 0 to 15 days, the counts obtained by the liquid scintillation measurement are basically unchanged, indicating that the present invention can detect 90 Sr plastic flash resin has good time stability.

[0055] (7) Detectable 90 The influence of particle size of Sr plastic flash resin on detection effect The detectable nanoparticles prepared in Example 1 were analyzed according to the following methods: less than 100 μm, 100-200 μm, and 200-300 μm. 90 The particle size classification of Sr plastic flash resin is carried out according to the method (5) above. 90 Detection of Sr can be detected 90 The influence of the particle size of Sr plastic flash resin on the detection effect is as follows Figure 7 As shown. It can be seen that the detectable 90 Sr plastic flash resin 90 There is no significant difference in the detection efficiency of Sr, among which 100~200 μm can be detected 90 Sr plastic flash resin has the highest detection efficiency.

[0056] (8) Detectable under different acidity conditions 90 Adsorption effect of Sr-containing plastic resin on strontium Weigh 50 mg of the detectable 90 Place the Sr-free plastic flash resin into a centrifuge tube, add 5 mL of strontium solution (strontium concentration is 1 ppm), and use nitric acid solution to adjust the acidity of the strontium solution. After sealing, place it in an oscillator and shake it at 25°C for 24 hours. After taking it out, filter the solution through a 0.22μm filter membrane and use ICP-OES (inductively coupled plasma emission spectrometer) to measure the strontium concentration in the solution after adsorption. Calculate the adsorption rate according to formula 1: Formula 1; Where C0 is the initial strontium concentration of the added strontium-containing solution (i.e. 1 ppm), C e is the concentration of strontium in the solution after resin adsorption.

[0057] Example 1 Preparation of detectable 90 The adsorption effect of Sr plastic flash resin on strontium under different acidity conditions is as follows Figure 8 As shown. It can be seen that the detectable 90The Sr plastic flash resin has the best adsorption effect on strontium under the acidity of 0.5~1 mol / L, and the adsorption rate under the acidity of 1 mol / L is 86.45%. 90 Sr plastic flash resin is suitable for the adsorption of strontium under low acidity conditions.

[0058] (9) Detectable 90 Sr plastic flash resin 90 Calculation of Sr detection efficiency Example 1 Preparation of detectable 90 The liquid scintillation measurement results of Sr plastic scintillation resin are shown in Table 1.

[0059] Table 1 Liquid scintillation measurement results

[0060] From the experimental results in Table 1, we can see that 90 When the Sr addition activity is 6.72 Bq, it can be detected 90 Sr plastic scintillation resin, measured by liquid scintillation counter 90 The detection efficiency of Sr is 91.32% (detection efficiency = actual measured 90 Sr count / added to the resin column 90 This shows that the detectable 90 Sr plastic flash resin 90 Sr has a very good detection effect.

[0061] (10) Comparison of Example 1 and Comparative Example 3 90 Comparison of Sr detection efficiency The detection efficiency experimental process of comparative example 3 is consistent with that of embodiment 1, and the specific measurement results are shown in Table 2. The comparison of detection efficiency between embodiment 1 and comparative example 3 is shown in Table 3.

[0062] Table 2 Comparative Example 3 Liquid scintillation measurement results

[0063] Table 3 Comparison of detection efficiency between Example 1 and Comparative Example 3

[0064] It can be seen that the detectable 90 The detection efficiency of the Sr plastic flash resin (91.32%) is much higher than the detection efficiency of the resin described in Comparative Example 3 (36.97%). 90 The detection of Sr has been significantly improved.

[0065] (11) Comparison of Strontium Adsorption Rates in Examples 1 to 4 Fig. 9 The adsorption amount of strontium by Example 1 (25% strontium extractant), Example 2 (15% strontium extractant), Example 3 (35% strontium extractant), and Example 4 (45% strontium extractant) is compared. Fig. 9 It can be seen that with the increase of extractant content, the detectable 90 The adsorption rate of Sr plastic flash resin to strontium increases, but when the extractant content is greater than 35%, increasing the extractant content can detect 90 The adsorption rate of Sr plastic flash resin did not increase significantly.

[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A detectable 90 Sr plastic flash resin, characterized in that It comprises a plastic scintillating microsphere and a strontium extractant located on the surface and internal pores of the plastic scintillating microsphere; The plastic scintillation microspheres include a plastic matrix and a scintillator dispersed in the plastic matrix; The strontium extractant is N,N,N',N'-tetraisobutyl-3-oxoglutaramide.

2. The detectable 90 Sr plastic flash resin, characterized in that The material of the plastic matrix is ​​one or more of polystyrene, styrene-divinylbenzene copolymer, polydivinylbenzene and polyvinyltoluene; The scintillator is one or more of 2,5-diphenyloxazole, 2-(4-biphenylyl)-5-phenyloxadiazole and 2-(4-biphenylyl)-5-(4-tolyl)-1,3,4-oxadiazole.

3. The detectable 90 Sr plastic flash resin, characterized in that The mass of the scintillator is 0.5-3% of the mass of the plastic substrate.

4. The detectable 90 Sr plastic flash resin, characterized in that The particle size of the plastic scintillation microspheres is 100-300 μm.

5. The detectable 90 Sr plastic flash resin, characterized in that The mass of the strontium extractant is 15-50% of the mass of the plastic scintillation microspheres.

6. The detectable method according to any one of claims 1 to 5 90 The method for preparing Sr plastic flash resin is characterized in that: The following steps are involved: (1) Mixing an unsaturated plastic monomer, a scintillator and an initiator to obtain an oil phase mixed liquid; (2) heating and mixing the emulsifier and water to obtain an aqueous phase mixture; (3) adding the oil phase mixed liquid to the water phase mixed liquid to carry out a polymerization reaction to obtain plastic scintillation microspheres; (4) mixing the plastic scintillation microspheres with an alcohol solution of a strontium extractant, removing the alcohol solvent after the strontium extractant is adsorbed by the plastic scintillation microspheres, and obtaining a detectable 90 Sr plastic flash resin; There is no order of precedence for steps (1) to (2).

7. The preparation method according to claim 6, characterized in that: The polymerization reaction temperature is 70-90°C and the reaction time is 6 h.

8. The preparation method according to claim 6, characterized in that: The alcohol solvent is removed by rotary evaporation at a temperature of 50-70°C.

9. The detectable method according to any one of claims 1 to 5 90 Sr plastic flash resin or the detectable 90 Sr plastic flash resin in adsorption and detection 90 Application in Sr.

10. The use according to claim 9, characterized in that: The adsorption 90 Sr was tested in a 0.5~1 mol / L nitric acid environment.

Citation Information

Patent Citations

  • Elution-extracting resin using amide compound as extracting agent and preparation method thereof

    CN101139418A

  • Scintillation resin with dual functions of separating and detecting strontium-90 as well as preparation method and application of scintillation resin

    CN117024642A

  • Plastic scintillator

    RU2012904C1